Humanized NOG mice as a model for tuberculosis vaccine‐induced immunity: a comparative analysis with the mouse and guinea pig models of tuberculosis. Issue 1 (19th June 2017) - Grover, Ajay; Troy, Amber; Rowe, Jenny; Troudt, JoLynn M.; Creissen, Elizabeth; McLean, Jennifer; Banerjee, Prabal; Feuer, Gerold; Izzo, Angelo A.
Summary: The humanized mouse model has been developed as a model to identify and characterize human immune responses to human pathogens and has been used to better identify vaccine candidates. In the current studies, the humanized mouse was used to determine the ability of a vaccine to affect the immune response to infection with Mycobacterium tuberculosis . Both human CD4 + and CD8 + T cells responded to infection in humanized mice as a result of infection. In humanized mice vaccinated with either BCG or with CpG‐C, a liposome‐based formulation containing the M. tuberculosis antigen ESAT‐6, both CD4 and CD8 T cells secreted cytokines that are known to be required for induction of protective immunity. In comparison to the C57BL/6 mouse model and Hartley guinea pig model of tuberculosis, data obtained from humanized mice complemented the data observed in the former models and provided further evidence that a vaccine can induce a human T‐cell response. Humanized mice provide a crucial pre‐clinical platform for evaluating human T‐cell immune responses in vaccine development against M. tuberculosis . Abstract : Investigation regarding the use of humanized mice to assess tuberculosis vaccines.